The effect of public target on the public-private partnership (PPP) residential development - Liu, Yong; Xu, Yelin; Wang, Ziyou (International Journal of Strategic Property Management, 2018)
A growing importance of public-private partnership (PPP) in public housing projects has drawn much attention. This paper presents a theoretical analysis exploring the effect of the public target on the private’s optimal strategy in a PPP housing project. An option-based model is established to show that an increase in the proportion of public housing will delay the project development. It indicates that the government needs to consider the trade-off between the waiting time and the supply of public housing. On the other hand, due to the delay effect, the expected project value would rise because the private developer is willing to wait for a better environment in the presence of a rise in public housing. Both private and public sector can benefit from this accurate evaluation model and its implications.